Effect of Plant Parts and Harvest Period on Rutin, Quercetin, Total Phenol Contents and Antioxidant Activity of Buckwheat (Fagopyrum esculentum Möench) Cultivated in Turkey - Acar, Ramazan; Unver, Ahmet; Arslan, Derya; Musa Ozcan, Mehmet; Gunes, Ahmet (Asian Journal of Chemistry, 2011)
The rutin, quercetin, total phenol contents and antioxidant activity of different parts of buckwheat (Fagopyrum esculentum) harvested at the different growing period in year 2009 were determined. Harvest period and plant parts had affected on these bioactive properties (p < 0.01). Rutin values ranged from 1874.97 (stem) to 3329.99 (leaf) mg/g. Quercetin contents were found between 2.20 and 29.33 mg/g. The phenol contents ranged between 24261.82 mg (flower) to 2989.10 mg (stem). The DPPH inhibition of flower, leaf, root and stem were established as 89.71, 73.57, 56.70 and 50.85 %, respectively. While quercetin decreased toward the end of harvest period, it was increased in root.